Mapping gender in ancient religious discourses - Penner, Todd C.; Vander Stichele, Caroline. (Biblical interpretation series, 2007)
This collection of essays focuses on issues related to gender at the intersection of religious discourses in antiquity. To that end, an array of traditions is analyzed with the aim of more fully situating the construction and representation of gender in early Christian, Jewish and Greco-Roman argumentation. Taken as a whole, these essays contribute to the goal of displaying the wide range of options that are available for examining the interconnection of gender, rhetoric, power, and ideology, especially as they relate to identity formation in the ancient world during the early centuries of the common era. The focus on ancient conceptions of gender makes this collection particularly useful not only for biblical scholars, but also for classicists and researchers working in the field of gender studies, as well as for those interested in exploring similar issues in other religious traditions or in Western religious traditions of different time periods.